COOPERATIVE POWER EXCHANGE BETWEEN TWO ROOFTOP SOLAR PLANTS INTERFACED WITH ARDUINO IOT CLOUD - Pragada Dheeraj Abhinav; Gorantla Anil Kumar; Sunkara Veerababu (Proceedings on Engineering Sciences)
The main aim of this paper is to develop a system which enables the sharing of excess power generated by the solar panels to maximize the use of renewa-ble energy sources and reduce the reliance on traditional power grids. The monitoring system collects data from the two rooftop solar plants and trans-mits it to the cloud for visualization, retrieval, and data storage. The Arduino IOT Cloud provides a platform for the monitoring of power generation and consumption, and the Node MCU ESP8266 enables communication between the two solar plants. The system implements a cooperative power exchange algorithm that allows the two rooftop solar plants to exchange power based on their energy production levels. The system operates on a peer-to-peer instantaneous energy monitoring, where the two rooftop solar plants can share excess power to each other.